3D printing of a high protein yoghurt-based gel: Effect of protein enrichment and gelatine on physical and sensory properties. (September 2021) - Riantiningtyas, Reisya Rizki; Sager, Valeska F.; Chow, Ching Yue; Thybo, Camilla D.; Bredie, Wender L.P.; Ahrné, Lilia
Graphical abstract: Highlights: 3D printed yoghurt gels were formulated using whey protein isolate and gelatine. Whey protein isolate and gelatine significantly affected rheology and printability. Addition of 12% WPI improved the printability at high gelatine concentration. Multisensory design provided positive indication of improved sensory acceptance. Abstract: The potential application of 3D printing technology in creating protein-rich desserts with multisensory design was investigated. Yoghurt-gel inks were formulated by varying the concentration of gelatine and whey protein isolate (WPI). Assessment of rheological and textural properties prior to printing, showed that an increase of gelatine concentration from 7.5 to 12.5% w/w increased the yield stress, storage modulus, loss modulus, firmness, and resilience of yoghurt gels. Addition of 12% WPI reduced these effects; creating softer gels with reduced resilience. However, these gels showed stable shape after printing, especially in formulations with higher gelatine concentrations. The changes in textural properties caused by the extrusion process need to be considered when designing yoghurt gels, as a significant reduction in firmness and resilience and an increase in adhesiveness were observed after 3D printing. The more stable and well-shaped 3D printed yoghurt gels were obtained by the combined effect of WPI and gelatine which provided a good balance of appearance, taste, flavour, and mouthfeel attributes evaluated by a trained sensory panel. A consumer study performed with thirty healthy adults showed the potential to improve sensory acceptance through the creation of multisensory layered design.